Students Perceived Quality of a Self-Created Mathematics Game-Based Materials - Rosillo, Ril D. (S&Co Publishing, 2022)
This study determined the quality of games students perceived for the game-based materials they develop after they experience playing a mathematics gameboard. The participants in this study were 88 students in 11th-grade Senior High School composed of 40 students in Sohoton General Academic Strand and 48 students in Kanlanuk Technical-Vocational Livelihood, selected through convenience non-random sampling. Through created games by students, it removed the presence of boredom that improved their performance. It impaired other competencies such as retention and automaticity of information from long-term memory. Moreover, students have developed the competitive, cooperative, and meaningful characteristics of the games, which was considered helpful in improving their knowledge based on how they perceived its' characteristics are important to contain in the game, and their confidence to participate in the lessons. Results from the classical item and test analysis spreadsheet revealed that the prior knowledge of the students increased after the interventions were made and implemented. The characteristics of the game were considered helpful to improve students’ knowledge and confidence in the lessons. These results have implications for in-depth study and analysis to have conclusive results regarding the influence of the intervention in enhancing students’ creativity.